IP3R1 deficiency in the cerebellum/brainstem causes basal ganglia-independent dystonia by triggering tonic Purkinje cell firings in mice - Hisatsune, Chihiro; Miyamoto, Hiroyuki; Hirono, Moritoshi; Yamaguchi, Naohide; Sugawara, Takeyuki; Ogawa, Naoko; Ebisui, Etsuko; Ohshima, Toshio; Yamada, Masahisa; Hensch, Takao K.; Hattori, Mitsuharu; Mikoshiba, Katsuhiko (Frontiers in Neural Circuits, 2013)
The type 1 inositol 1,4,5- trisphosphate receptor (IP3R1) is a Ca2+ channel on the endoplasmic reticulum and is a predominant isoform in the brain among the three types of IP3Rs. Mice lacking IP3R1 show seizure-like behavior; however the cellular and neural circuit mechanism by which IP3R1 deletion causes the abnormal movements is unknown. Here, we found that the conditional knockout mice lacking IP3R1 specifically in the cerebellum and brainstem experience dystonia and show that cerebellar Purkinje cell (PC) firing patterns were coupled to specific dystonic movements. Recordings in freely behaving mice revealed epochs of low and high frequency PC complex spikes linked to body extension and rigidity, respectively. Remarkably, dystonic symptoms were independent of the basal ganglia, and could be rescued by inactivation of the cerebellum, inferior olive or in the absence of PCs. These findings implicate IP3R1-dependent PC firing patterns in cerebellum in motor coordination and the expression of dystonia through the olivo-cerebellar pathway.